Dynamics and epitope specificity of anti-human leukocyte antibodies following renal allograft nephrectomy. Issue 8 (19th April 2016) - Lachmann, Nils; Schönemann, Constanze; El-Awar, Nadim; Everly, Matthew; Budde, Klemens; Terasaki, Paul I.; Waiser, Johannes
Abstract: Background: A considerable proportion of patients awaiting kidney transplantation is immunized by previous transplantation(s). We investigated how allograft nephrectomy (Nx) and withdrawal of maintenance immunosuppression (WD-MIS) in patients with a failed renal allograft contribute to allosensitization. Methods: HLA antibodies (HLAabs) were analyzed before and after Nx and/or WD-MIS using a single antigen bead assay. Patients were grouped as follows: (A) Nx and concomitant WD-MIS ( n = 28), (B) Nx ( n = 14) and (C) WD-MIS ( n = 12). In a subgroup of patients, the epitope specificity of HLAabs was determined by adsorption and elution of sera with recombinant single HLA allele–expressing cell lines. Results: Following Nx and/or WD-MIS, HLAabs were detectable in 100, 100 and 92% of patients in Groups A, B and C, respectively. In patients of all groups, de novo donor-specific HLAabs (DSAs) were found. After Nx, an increase in the breadth [percent panel reactive antibody (%PRA)] and mean fluorescence intensity of class I HLAabs was predominant. In contrast, an increase of class II HLAabs prevailed following WD-MIS. Experimental analysis of the epitope specificities revealed that 64% of the class I HLAabs classically denoted as non-DSA were donor epitope-specific HLAabs (DESA). Conclusions: Both Nx and WD-MIS contribute to alloimmunization with differing patterns concerning class I and II HLAabs. Nx preferentially increased class I HLAabs and most of the observed class I HLAabs were DESA. Considering that class I, but not class II, HLA molecules are constitutively expressed, our results support the hypothesis that the increase of HLAabs following Nx might have been caused by removal of the adsorbing donor tissue (sponge hypothesis).